Recent Multilateral Debt Restructurings with Offcial and Bank Creditors - Brau, Eduard (Occasional Papers; Occasional Paper ;, 1983)
Experience with multilateral debt restructurings with official creditors and with international banks in the second half of the 1970s was described in External Indebtedness of Developing Countries, issued in 1981. The present paper reviews recent developments, covering the period through early October 1983.